The Lessons of Asilomar and the H5N1 “Affair” - Stanley Falkow (American Society for Microbiology, 2012)
ABSTRACT In mid-1974, soon after the first recombinant DNA molecules were replicated in Escherichia coli, scientists called for, and observed, a voluntary moratorium on certain experiments. One goal of the moratorium was to hold a conference (Asilomar) to evaluate the risks, if any, of this new technology. The Asilomar conference concluded that recombinant DNA research should proceed but under strict guidelines. The furor surrounding the recent genetic manipulation of the transmissibility of avian influenza virus H5N1 led to a short-term moratorium that has been extended indefinitely. The question is how long should the moratorium remain in place, or should it be permanent? Voltaire observed, “History never repeats itself; man always does.” I believe the parallels of Asilomar can be applied to the problem facing biomedical science today. We should move forward to establish standardized guidelines, using common sense and scientific creativity. The onus of responsibility falls on the individual scientist and involves the education of a new generation of scientists into the social and ethical implications of genetic engineering in a new age of genomics and synthetic biology. In addition, scientists who work with infectious agents must deal not only with biosafety but also, alas, with bioterrorism. The H5N1 “affair” is not a question of freedom of inquiry or the dissemination of scientific research; it is a question of the social responsibility of science and scientists to ensure that the public understands why this work is beneficial and worthwhile.